2014
DOI: 10.1590/0034-737x201461040008
|View full text |Cite
|
Sign up to set email alerts
|

Levantamento fitossociológico de plantas daninhas em pastagens degradadas do Médio Vale do Rio Doce, Minas Gerais

Abstract: O levantamento fitossociológico é uma ferramenta importante, na análise do impacto que os sistemas de manejo e as práticas agrícolas exercem sobre a dinâmica de crescimento e ocupação das plantas daninhas no agroecossistema. Por essa razão, esta pesquisa teve como objetivo realizar a caracterização fitossociológica de plantas daninhas, em oito áreas de pastagens degradadas, de cinco municípios do Médio Vale do Rio Doce, em Minas Gerais. No total foram identificadas 68 espécies, pertencentes a 18 famílias, send… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 16 publications
2
11
0
11
Order By: Relevance
“…On grazing areas, the diversity was low, since this is a very peculiar, poorly managed and compacted environment, determining that only the species with higher adaptation capacity to these conditions will germinate and proliferate. Ferreira et al (2014), when studying the diversity of weeds on degraded grazing areas on different locations of the Médio Vale do Rio Doce, observed a large diversity across the studied areas; however, within each location, there was a higher diversity on some places and, on others, the diversity was very low. Jakelaitis et al (2014) found low values for Shanonn's index (between 1.33 and 1.70) on cultured areas with pastures.…”
Section: Resultsmentioning
confidence: 90%
“…On grazing areas, the diversity was low, since this is a very peculiar, poorly managed and compacted environment, determining that only the species with higher adaptation capacity to these conditions will germinate and proliferate. Ferreira et al (2014), when studying the diversity of weeds on degraded grazing areas on different locations of the Médio Vale do Rio Doce, observed a large diversity across the studied areas; however, within each location, there was a higher diversity on some places and, on others, the diversity was very low. Jakelaitis et al (2014) found low values for Shanonn's index (between 1.33 and 1.70) on cultured areas with pastures.…”
Section: Resultsmentioning
confidence: 90%
“…In Brazil, these species have been basically controlled through herbicide application (Ferreira et al, 2014). The herbicide aminopyralid + fluroxypyr, whose mechanism of action is to mimic auxin, interferes in the apical meristem of plants, thus affecting the division of tissues; it has been used in Brazil to control these weeds in pasture areas.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, changes in the composition of weed communities were also observed in different agricultural crops, such as sugarcane (Kuva et al, 2007;Soares et al, 2011), pastures (Ferreira et al, 2014), bean (Tavares et al, 2013), cover crops (Lima et al, 2014;Lamego et al, 2015), manioc (Cardoso et al, 2013;Soares et al, 2015), corn (Correa et al, 2011), corn intercropped with legumes (Oliveira et al, 2014) and corn intercropped with forage (Batista et al, 2014;Concenço et al, 2015), millet (Teodoro et al, 2015), lettuce (Ferreira et al, 2013), Jatropha curcas (Concenço et al, 2014) and coffee under organic management (Maciel et al, 2010a;Partelli et al, 2010).…”
Section: Cynodon Dactylon and Ipomoea Grandifoliamentioning
confidence: 89%